(untitled) (Annals of Medical Research, 2022)
Aim: Large breasts create psychological and physical problems in women, all of whom must also keep in mind the common problem of breast cancer. In the present study we examine the effect of breast reduction surgery on breast cancer risk. Materials and Methods: Our retrospective study is based on the records (between June 1, 2014, and June 30, 2019) of patients who underwent breast reduction surgery in the Plastic, Reconstructive and Aesthetical Surgery clinic of a training and research hospital. Statistical analyses were conducted using IBM SPSS Statistics (Version 25.0. Armonk, NY: IBM Corp.). Normal distribution of the data was analyzed with Kolmogorov-Smirnov. The data assessment included descriptive statistical methods and Kruskal-Wallis test. The results were evaluated at a 95% confidence interval and a significance level of p <0.05. Results: Of the 134 patients included in the study, 47% were aged 36–50 years and 60.4% had a body mass index of ≥40. The shortest follow-up was 4 years, the longest follow-up was 9 years and the mean follow-up was 5.5 years. The mean amount of tissue removed from the right breast was 1050.54±484.90, the mean amount of tissue removed from the left breast was 1059.54±522.28, and the mean length of hospital stay was 1.15±0.74 days. The pedicle of choice was superomedial in 55.2% and the inverted-T scar technique was used in 66.4%. Definitive findings of neither in-situ nor invasive cancer were identified in any of the cases. Conclusion: Despite major sequelae such as external permanent scarring and decrease in breastfeeding and nipple sensation, breast reduction surgery is the operation that records the highest patient satisfaction in plastic, reconstructive and aesthetica surgery, as it provides physical and psychological relief by eliminating the heavy weight that affects the shoulders, back and neck. It is also known that the risk of breast cancer is decreased due to the removal of a considerable amount of breast tissue with cancer potential from the body, as well as the early diagnosis and treatment of incidentally detected cancer cases, albeit at a low rate. This is also supported by our findings.